Cerebral complications induced by calcineurin inhibitors in children after haematopoietic stem cell transplantation - Piątkowska, Magdalena; Wysocki, Mariusz; Styczyński, Jan (Contemporary Oncology/Współczesna Onkologia, 2011)
Calcineurin inhibitors (CI), such as tacrolimus and cyclosporin A (CSA), are routinely used for prophylaxis and therapy of graft- versus -host disease (GVHD) after haematopoietic stem cell transplantation (HSCT) and solid organ transplantation. Neurotoxicity is a well-known side effect of calcineurin inhibitor therapy with multifactorial pathogenesis. In this paper we report the clinical and radiological features of CI-induced cerebral complications in four paediatric patients after haematopoietic stem cell transplantation. The most common symptoms in this series of patients were seizures and disturbances of consciousness. Abnormalities in neuroimaging suggested CI-induced leukoencephalopathy or reversible posterior leukoencephalopathy syndrome or showed cerebral haemorrhage. Other possible causes of neurological complications, such as delayed cyclosporin A toxicity, post-transplant microangiopathy, hypertension or thrombocytopenia are discussed. We also present a review of the literature of tacrolimus-induced neurotoxicity in children. So far, 47 case reports of children and adolescents up to 21 years of age with tacrolimus-induced encephalopathy have been described in the literature. The clinical features of tacrolimus-induced leukoencephalopathy in children are similar to those reported in adults.